Areas of endemism of arthropods in the Atlantic Forest (Brazil): an approach based on a metaconsensus criterion using endemicity analysis. (7th April 2016) - Hoffmeister, Camila Hendges; Ferrari, Augusto
Abstract : An analysis of endemicity (NDM/VNDM) based on 6541 records from 791 species of arthropods was conducted aiming to delimitate areas of endemism (AEs) in the Atlantic Forest (Brazil). Nine analyses were run employing different analytical parameters of grid size and data extrapolation of species distribution, and their effects on the results were observed. The present study is the first to employ an analysis of sensitivity with UPGMA (unweighted pair group method with arithmatic mean) as a metaconsensus criterion to compare and select AEs resulting from analyses of endemicity with different analytical parameters. In total, 724 AEs grouped into 313 consensus areas were identified. With the metaconsensus criterion, 29 groups of areas were defined, most of them coinciding with the areas obtained in other studies, which confirms that the metaconsus criterion is a clear and objective method for comparing and selecting AEs. The results of the present imply that species of arthorpods respond differently to events and, moreover, that the geographical/climate features usually employed to explain distributional patterns of other taxa do not uniformly affect all species included in the study. The AEs identified in the present study represent a major advance in the search for quantitative distribution patterns in the Atlantic Rainforest, contributing to studies of historical biogeography and other approaches related to the conservation.